1867 Nev. Stat. 66 - (:unkn) unknown (My University, 1867)
Ch. 30, § 1: Prohibited the concealed carry of any dirk, pistol, sword in a cane, slung-shot, or other dangerous or deadly weapon, concealed. Violators guilty of a misdemeanor, imprisoned not less than thirty nor more than ninety days, or fined not less than twenty nor more than two hundred dollars.
Keywords: CARRY - CONCEALED